Effects in the population inversion of3H4 level in Tm, Tm-Tb and Tm-Eu doped germanate glasses for amplifiers applications - Librantz, A. F H; Gomes, L.; Pairier, G. [UNESP]; Ribeiro, S. J L [UNESP]; Messaddeq, Y. [UNESP] (SPIE, the international society for optics and photonics, 2006)
The population inversion of the Tm3+ in GLKZ glass involved in the 1470 nm emission (3H4 → 3F 4) as a function of Tb (or Eu) concentration was calculated by computational simulation for a CW laser pumping at 792 nm. These calculations were performed using the experimental Tm→Tb an Tm→Eu transfer rates and the spectroscopic parameters of the Tm (0.1 mol %) system. The result shows that 0.2 mol % (Tb3+) and 0.4 mol % of Eu3+ ions propitiate best population inversion of Tm3+ (0.1 mol %) maximizing the amplification coefficient of germanate (GLKZ) glass when operating as laser intensity amplification at 1470 nm. Besides the effective deactivation of the 3F4 level, the presence of Tb3+ or Eu 3+ ions introduce a depopulation of the 3H4 emitting level by means of a cross relaxation process with Tm3+ ions. In spite of this, the whole effect is verified to be benefic for using Tm-doped GLKZ glass codoped with Tb3+ or Eu3+ as a suitable material for confectioning optical amplifiers that operates in the S-band for telecommunication.
Keywords: Germanate glasses; Laser intensity amplification; Population inversion; Spectroscopic parameters; Computer simulation; Continuous wave lasers; Doping (additives); Germanium compounds; Glass; Pumping (laser); Light amplifiers